M-Payments, Financial Inclusion, and Full Market Coverage - Vladimir A. Karamychev; Jean-Marie Viaene (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Mobile payments (m-payments) increase the accessibility of large segments of society to financial services while before the traditional banking system excluded these for lack of proof of identity and because of unsafe environments. This constitutes a key driver of new growth strategies of the developing world. Smartphones are essential to perform m-payments. In that regard, recent criticism from different sides has expressed the view that manufacturers' strategies generate partial market coverage whereby the purchase of a phone and financial inclusion also remain out of reach for the group of poor consumers. Our aim in this paper is to examine the theoretical premises of this conjecture in a small open economy and uncover the conditions under which full market coverage is efficient and desirable. We analyze subgame perfect equilibria of a vertical duopoly model characterized by consumers' taste for quality. The government uses taxes and/or subsidies to modify the market equilibrium. Given this, the following issues are considered: (a) What is the impact of different standards of payment security on the equilibrium number of low- and high-quality users? (b) What are the aggregate welfare gains of complete financial inclusion? (c) What happens if phone makers are foreign?
Keywords: F23; G50; H31; H62; L13; L15; 330; vertical duopoly; full market coverage; technical obsolescence; financial inclusion